Zdhhc2 Is Essential for Plasmacytoid Dendritic Cells Mediated Inflammatory Response in Psoriasis - Zhou, Binhui; Yang, Wenyi; Li, Wushan; He, Le; Lu, Liaoxun; Zhang, Lichen; Liu, Zhuangzhuang; Wang, Ying; Chao, Tianzhu; Huang, Rong; Gu, Yanrong; Jia, Tingting; et al. (Frontiers in Immunology, 2021)
Zdhhc family genes are composed of 24 members that regulate palmitoylation a post-translational modification process for proteins. Mutations in genes that alter palmitoylation or de-palmitoylation could result in neurodegenerative diseases and inflammatory disorders. In this study, we found that Zdhhc2 was robustly induced in psoriatic skin and loss of Zdhhc2 in mice by CRISPR/Cas9 dramatically inhibited pathology of the ear skin following imiquimod treatment. As psoriasis is an inflammatory disorder, we analyzed tissue infiltrating immune cells and cytokine production. Strikingly we found that a master psoriatic cytokine interferon-α (IFN-α) in the lesioned skin of wildtype (WT) mice was 23-fold higher than that in Zdhhc2 deficient counterparts. In addition, we found that CD45+ white blood cells (WBC) infiltrating in the skin of Zdhhc2 deficient mice were also significantly reduced. Amelioration in psoriasis and dramatically reduced inflammation of Zdhhc2 deficient mice led us to analyze the cellular components that were affected by loss of Zdhhc2. We found that imiquimod induced plasmacytoid dendritic cell (pDC) accumulation in psoriatic skin, spleen and draining lymph nodes (DLN) were drastically decreased in Zdhhc2 deficient mice, and the expression of pDC activation marker CD80 also exhibited significantly inhibited in psoriatic skin. In further experiments, we confirmed the cell intrinsic effect of Zdhhc2 on pDCs as we found that loss of zDHHC2 in human CAL-1 pDC dampened both interferon regulatory factor 7 (IRF7) phosphorylation and IFN-α production. Therefore, we identified novel function of Zdhhc2 in controlling inflammatory response in psoriasis in mice and we also confirmed that crucial role of Zdhhc2 in pDCs by regulating IRF7 activity and production of the critical cytokine. Our results finding the dependence of IFN-α production on Zdhhc2 in inflamed murine skin and in human pDCs provide rationale for targeting this new molecule in treatment of inflammation.